Pelatihan Penanaman Toga Sebagai Upaya Trauma Healing bagi Siswa SD Terdampak Gempa Bumi Cianjur - Kismiati, Dyah Aniza; Hutasoit, Leonard R.; Wahyuningsih, Tri; Ratnaningsih, Anna; Sekarwinahyu, Mestika (Jurnal Pengabdian UNDIKMA, 2023)
This community service activity aims to eliminate the trauma of children affected by the earthquake through family medicinal plant planting (TOGA) activities at SD Negeri Sukamaju 1 Cianjur Regency. This method of implementing service uses training consisting of 3 stages of activities, namely, the preparation stage, the implementation stage and the evaluation stage. This activity is held in 2 ways, namely through the delivery of TOGA material in the classroom and TOGA planting practice activities in the schoolyard. The activity was also interspersed with ice breaking, namely by doing happy gymnastics guided by the facilitator lecturers. This activity evaluation instrument uses pre-test and post-test and is then analyzed descriptively. The results of this service show that there is an increase in students’ insight into TOGA, which can be seen from the increase in post-test results by 10%. In addition, students have the skills to plant and care for family medicinal plants (TOGA).